Komunikasi Penyiaran Pada Program Berita “Nusa Tenggara Barat Hari Ini” - Yanti, Komang Yogi; Juniawan, Ida Bagus Heri; Jelantik, Sayu Kadek (IAHN Gde Pudja Mataram, 2023)
Broadcast communication in the digital era, especially television media, has experienced very strict selection in the last few decades. Media corporations compete fiercely to captivate viewers with news coverage that provides insight and conveys information to the public. The West Nusa Tenggara TVRI News Program still exists to this day, although so far it has received little attention from the public. This research aims to identify the form, process and impact of broadcast communication on the news program